Staying Calm and Well in the Midst of the COVID-19 Storm: One University's Longitudinal Outcomes Evaluation of a Mental Health and Well-Being Webinar Series - Bernadette Mazurek Melnyk; Megan Amaya; Andreanna Pavan Hsieh; Rebecca Momany; Josh Winn; Logan J. Forbes (The Ohio State University Libraries, 2021)
Background: As the COVID-19 pandemic began, wellness leadership at a large Mid-west public university anticipated an increase in mental health problems among faculty and staff. A two-part weekly webinar series entitled "Staying Calm and Well in the Midst of the COVID-19 Storm" was launched to assist faculty and staff in coping with stressful issues related to the pandemic and enhancing their well-being. This series provided the university community with evidence-based knowledge, skills, and resources to enhance their ability in taking good self-care. Aim: To assess participant mental health outcomes during the two-part mental health and well-being educational webinar series over time. Methods: A longitudinal outcomes evaluation was conducted. Evaluation data was obtained from the participants via an anonymous post-webinar survey, which included questions from the Patient-Health Questionnaire-4 (PHQ-4) to assess symptoms of anxiety and depression. The first series was conducted over the course of 8 weeks and the second series took place over 7 weeks. Descriptive statistics were used to assess responses to the PHQ-4 over time to evaluate outcomes of the webinar series. An open-ended question also asked participants about the 2 to 3 biggest concerns and worries they had at that moment.    Results: The average amount of survey responses received were 1,470.25 (SD = ± 240.3) for Series One and 926.4 (SD = ± 164.3) for Series Two. Ninety-five percent of participants put the skills they learned during both series into practice. When participants reported experiencing anxiety or depressive symptoms, they most frequently reported experiencing them several days a week. The number of participants reporting no depressive or anxiety symptoms increased as the webinar series progressed over time. The types of concerns and worries reported varied across time. Conclusion: The Staying Calm and Well During the COVID-19 Pandemic webinar participants had a reduction in symptoms associated with anxiety and depression after completing the series.